Surgical Removal of Impacted Lower Second Molar in Transverse Position: A Case Report - Jimmy Antonio Ascanoa Olazo; Miriam Arellanos-Tafur; Felix Rojas-Arquinego (Case Reports in Dentistry)
Conclusions: Retention of permanent second molars is rarely reported in the literature. It is advisable to apply all possible methods to position these teeth in the occlusal plane to ensure proper masticatory function. However, there are cases where extraction is necessary due to space limitations, and alternative solutions for replacing the lost tooth should be explored.